Post-event follow-up costs in patients with atherosclerotic cardiovascular disease in Spain - Martínez López, Icíar; Gómez Cerezo, Jorge Francisco; Gámez, José M.; Egocheaga Cabello, Isabel; Castellanos, Mar; Campuzano Ruiz, Raquel; Barrios, Vivencio; Pallarés-Carratalá, Vicente; Rodríguez, José Manuel; Morant Talamante, Nuria; Parrondo, Javier; Mostaza, José María (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Atherosclerotic cardiovascular disease (ASCVD) is one of the main causes of morbidity and mortality in developed countries and entails high resources use and costs for health systems. The risk of suffering future cardiovascular (CV) events and the consequent resources use is higher in those patients who have already had a previous cardiovascular event. The objective of the study was to determine the average annual cost of patients with a new or recurrent atherosclerotic CV event during the 2 years after the event. Methodology: Retrospective observational study of electronic medical records of patients from the BIG-PAC® database (7 integrated health areas of 7 Autonomous Communities; n=1.8 million). Patients with a new or recurrent episode of ASCVD (angina, acute myocardial infarction, transient ischemic attack, stroke, or peripheral arterial disease) between 1-Jan-2017 and 31-Dec-2018 were included. The resources use within two years of the diagnosis was estimated in order to estimate the average cost of patient follow-up. The costs derived from pharmacological treatments were obtained from the NHS pricing nomenclator database (https://www.sanidad.gob.es/profesionales/nomenclator.do) Results: A total of 26,976 patients with an ASCVD episode were identified during the recruitment period; Out of them, 6,798 had a recurrent event during the follow-up period and 2,414 died. The average costs per patient were €11,171 during the first year and €9,944 during the second year. Discussion: Patients with ASCVD represent a significant economic burden for the health system and for society. Despite the perception that drug costs in the follow-up of chronic patients imply a high percentage of the costs, these accounted for only one tenth of the total amount. Implementing preventive programs and increasing the control of cardiovascular risk factors may have a significant social and health impact by helping to reduce mortality and costs for the Spanish National Health System.